The Finger of God and the Forming of a Nation: The Origin and Purpose of the Decalogue - Baker, David L. (Tyndale bulletin, 2005)
The problem of the origin of the Decalogue is often expressed in terms of whether or not it is Mosaic or developed from a form that originated in the Mosaic period. Many scholars have argued for one or other of these positions, though recently some have suggested that the Decalogue was formulated much later in Israel’s history, during or even after the Exile. However none of these views engages seriously with the claim of the biblical text that the Decalogue was spoken directly by God to the people of Israel at Sinai and written by ‘the finger of God’ on the two stone tablets. In this article I will endeavour to do that, before considering the audience to whom the Decalogue was addressed, what it was intended to be for them, and the motives and sanctions which were stated or implied. I shall argue that this document was instrumental in the forming of Israel as a nation, indeed as the people of God, and that it contains the essential principles which underlie the detailed laws in Exodus, Leviticus and Deuteronomy.